2006
DOI: 10.1245/s10434-006-9098-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Accuracy of Breast Resection in Oncoplastic Surgery and Quadrantectomy in Breast Cancer

Abstract: Oncoplastic surgery achieves more accurate tumor resection than standard quadrantectomy. This approach might be useful in extending the indications for conservative therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(84 citation statements)
references
References 23 publications
3
77
1
2
Order By: Relevance
“…In this study, it is seen that OBS resulted in larger specimen volume size as well as wider mean margins being obtained. This is similar to the experience of other authors too [6][7][8]. In our patients, total excision was made possible by tattooing the tumor skin projection preoperatively as suggested by Mathieu et al [14].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, it is seen that OBS resulted in larger specimen volume size as well as wider mean margins being obtained. This is similar to the experience of other authors too [6][7][8]. In our patients, total excision was made possible by tattooing the tumor skin projection preoperatively as suggested by Mathieu et al [14].…”
Section: Discussionsupporting
confidence: 88%
“…Studies have demonstrated that in early breast cancers and large operable breast cancers, as compared to conventional breast conservation surgery (wide local excision or lumpectomy with a gross margin of 1 cm plus axillary lymph node dissection), OBS achieves wider excision of tumor, superior mean volume of specimen, and potentially reduces margin involvement. It is more effective from aesthetic-functional point of view and does not compromise local control and survival [6][7][8]. Locally advanced breast cancer (LABC) accounts for a large proportion of breast cancers in India; 40-60 % in some series.…”
Section: Introductionmentioning
confidence: 99%
“…The volume of each tumour was calculated using the following formula: tumour volume = (3.14/6) Â (histological size) and the volume of each specimen was calculated by multiplying measurements of the length, width and height. 8 Formalin-fixed and paraffinembedded sections were stained with haematoxylin and eosin for routine examination. The margins were assessed by a standardised radial (perpendicular) margin assessment technique in which six margins were taken (superior, inferior, medial, lateral, posterior, anterior).…”
Section: Pathologic Analysismentioning
confidence: 99%
“…Methods of BCS are classified into two groups as follows: Volume displacement using glandular transposition and volume replacement using autologous tissue (9,34,35). The method applied should be chosen based on the size of the defect and the breast.…”
Section: Discussionmentioning
confidence: 99%